Effects of a Short Half-Time Re-Warm-Up Program on Matches Running Performance and Fitness Test Performance of Male Elite Youth Soccer Players - Michail Christaras; Yiannis Michailidis; Athanasios Mandroukas; Lazaros Vardakis; Kosmas Christoulas; Thomas Metaxas (Applied Sciences, 2023)
The aim of the study was to investigate the effect of a half-time short re-warm-up (RW) strategy on the performance of young soccer players in tests of physical abilities and running performance during matches. Twenty-three players (under 17) participated in the study. Body temperature, 10 m sprint, 30 m sprint, the Illinois agility test, countermovement jump (CMJ), and squat jump (SJ) were measured, immediately post-warm-up. Then in one condition, the tests were repeated after a passive rest, and in the other condition, after a 12 min passive rest and 3 min RW. Furthermore, the RW was applied at half-time of two of the four matches where the running performance was measured in the first quarter of the two halves. The results showed that the two conditions differed significantly in the 10 m sprint and CMJ performances (p < 0.001 and p = 0.049, respectively). After the passive rest, a significant decrease in body temperature and performance in SJ was observed (p < 0.001 for both). No other differences were observed. In conclusion, the short RW program can limit the decrement in performance in power tests such as sprints and jumps.